Prevalence and risk factors of postpartum depression within one year after birth in urban slums of Dhaka, Bangladesh - Azad, Rashidul; Fahmi, Rukhshan; Shrestha, Sadichhya; Joshi, Hemraj; Hasan, Mehedi; Khan, Abdullah Nurus Salam; Chowdhury, Mohiuddin Ahsanul Kabir; Arifeen, Shams El; Billah, Sk Masum (PLOS ONE, 2022)
This article was published in the PLOS ONE [© 2019 Azad et al. This is an open access article distributed under the terms of the Creative Commons Attribution License ] and the definite version is available at: https://doi.org/10.1371/journal.pone.0215735 The Journal's website is at: https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0215735